Islamic Microfinance: Integrative Studies of Textual and Contextual of Qardul Hasn in Afghanistan - Ziaulrahman Mushkalamzai; Matiullah Taeb; Mohammad Wasim Hanif (Jurnal Hikmatuna, 2019)
Abstract Qardul Hasan is considering the most important tradition of microfinance loan in Islamic Sharia. Allah and Prophet Mohammad insist upon giving the Qardul Hasan in several verses and Hadiths. In the past few years, numerous Muslims developing countries have practiced an interesting phenomenon to build the country’s economy through Islamic Microfinance for empowerment of small communities. Therefore, it is supposed to be an important to investigate and provide much needed social service to the poor effectively. The Qardul Hasan eligible beneficiary will be considered and may categorized as the dhuafa’ and Weak group in the society. Thus, the purpose of this paper is to illustratethat why the attitude of Qardul Hasan is failure in poverty Alleviation in Afghanistan and how can be revived as an important instrument of Islamic Microfinance program to empower underprivilege people and Afghan oppressed community.